150k views
3 votes
The EXPAND equation of the polynomial function is f(x)= (x-2)(x-5)(x-sqrt3)(x+sqrt3) 15 POINTS Please explain as well if you can. Please

The EXPAND equation of the polynomial function is f(x)= (x-2)(x-5)(x-sqrt3)(x+sqrt-example-1

1 Answer

2 votes

Answer:

f(x) = x⁴ - 7x³ + 7x² + 21x - 30

Explanation:

Given function is f(x) = (x - 2)(x - 5)(x - √3)(x + √3)

f(x) = (x - 2)(x - 5)[(x² - (√3)²] {By using formula, (a - b)(a + b) = a² - b²]

= (x - 2)(x - 5)(x² - 3)

= (x - 2)[x(x² - 3) -5(x² - 3)] [By distributive property]

= (x - 2)(x³ - 3x - 5x² + 15)

= (x - 2)(x³ - 5x² - 3x + 15)

= [x(x³ - 5x² - 3x + 15) - 2(x³ - 5x² - 3x + 15)]

= x⁴ - 5x³- 3x² + 15x - 2x³ + 10x² + 6x - 30

= x⁴ - 7x³ + 7x² + 21x - 30

Therefore, expanded form of the polynomial function will be,

f(x) = x⁴ - 7x³ + 7x² + 21x - 30

User GJZ
by
5.0k points